Problems on the Gravitational Wave and the Repulsive Gravitation - Lo, C. Y. (JOURNAL OF ADVANCES IN PHYSICS, 2016)
It is exciting that the gravitational wave has been confirmed, according to the announcement of LIGO. This would be the time to fix the Einstein equation for the gravitational wave and the nonexistence of the dynamic solution. As a first step, theorists should improve their pure mathematics on non-linear mathematics and related physical considerations beyond Einstein. Then, it is time to rectify the Einstein equation that has no gravitational wave solution which Einstein has recognized, and no dynamic solution that Einstein failed to see. A problem is that physicists in LIGO did not know their shortcomings. Also, in view of the far distance of the sources, it is very questionable that the physicists can determine they are from black holes. Moreover, since the repulsive gravitation can also generate a gravitational wave, the problem of gravitational wave is actually far more complicated than we have known. A useful feature of the gravitational wave based on repulsive gravitation is that it can be easily generated on earth. Thus this can be a new tool for communication because it can penetrate any medium.